The importance of dental office management in times of COVID 19 and how to resume activities in post-pandemic. - Silva, João Maurício Ferraz da; Zanet, Caio Gorgulho; Trezza, Renato; Lamour, Luciane; Beraldo, André Luiz (Brazilian Dental Science, 2020)
We are going through a health crisis, a pandemic caused by the new corona virus (SarsCOV2), which causes the disease COVID 19. This pandemic has also had a negative impact on the world economy, with dental offices being directly affected. Given this, the objective of this article is to bring important points in the strategy of management of dental clinics and how to be prepared to face the moment of crisis and also for the resumption. We believe that actions should be guided on three fronts: survival, sustainability and new future. The scenario is new, but with the right actions, the prospects for recovery are good. The important thing is to stay focused on what we have control, to do our best for the financial health of the business, however, remember that human health comes first, that any financial recovery will only be positive when people’s lives and health are being preserved. Keywords Corona virus, business management, financial management.